Harvesting Large Fascia Lata Sheaths: A Rational Approach - Amir, Aharon (2000)
This article describes an “S”-shaped incision for the open approach of harvesting wide sheets of fascia lata with reference to the important anatomical landmarks. Forty-three patients required dural replacement in cases of tumors, trauma, or cerebrospinal fluid leak involving the anterior skull base. The extended anterior suberanial approach to the skull base was used for all patients. Early functional status of the operated limb in seven of the patients treated first was assessed by physical examination and then by means of the computerized Kinetic Communicator (Kin-Com; Medex Diagnostics, Canada) dynamometer. None of these patients suffered any significant immediate complications and had good results at the preliminary functional assessment. All other patients were evaluated clinically for functional deficits of the operated lower limb to further assess its morbidity. The technique described herein was shown to enhance the case and control of fascia lata harvesting. It affords low complication rate and donor limb morbidity. Donor limb morbidity did not have any deleterious effect on the patients' normal daily activities and only became apparent during strenuous physical activity.